Block periodization as an alternative approach to preparation of high-performance canoe/kayak paddlers - Issurin, V. G. (2009)
Presentation at the ICF Coaches` Symposium, Warsaw, 27.02-1.03.2009. Author presents • The traditional theory - criticism and restrictions, • The alternative approach: basics, facts and background and • Applications to the practice: recommendations.